Being where, with whom, and when it happens: spatial, interpersonal, and temporal presence while viewing live streaming of collegiate sports in virtual reality - Vincent, Andrew; Frewen, Paul (Frontiers in Virtual Reality, 2023)
INTRODUCTION: Although virtual reality (VR) is most popularly known for its applications to gaming, other entertainment applications are increasingly being explored including in the sports media industry, but little research has so far examined the experiences induced by VR viewing of a live sporting event. MATERIALS AND METHODS: Participants (n = 93) were university students who were approached in the context of a field study from a nearby community eatery area on the university campus to watch brief segments of a 360degree live stream of the home games of their university volleyball and basketball teams both while wearing and not wearing an inexpensive smart-phone based head-mounted display (HMD). Immediately afterward, participants then reported on their relative experience of spatial, social, and temporal presence, as well as their satisfaction-preference with each of the two viewing modalities, in response to brief face-valid screening questions. RESULTS: The majority of participants experienced greater presence while wearing the VR headset, and approximately one in every two reported preferring to watch the games in VR. Experiences of spatial, social, and temporal presence were correlated, with participants’ experience of spatial presence independently correlated with preferring to watch the games in VR. DISCUSSION: Media vendors should offer VR viewing of sports including via inexpensive, smart-phone mediated VR as an additional, cost-effective alternative means of heightening fans’ experience of virtual presence at the games when fans are unable to go to the games in person.